2011
DOI: 10.1007/s10509-011-0876-6
|View full text |Cite
|
Sign up to set email alerts
|

Universal characteristics of ion-acoustic wave dynamics in magnetized plasmas with emphasis on Tsallis distribution

Abstract: Using the extended Poincaré-Lighthill-Kuo (PLK) reductive perturbation method, which incorporates the phase-shift variations, it is shown that common features on propagation and head-on collisions of ion-acoustic waves exist for a magnetized plasmas of different inertial-less particle distributions. For instance it is remarked that, the soliton amplitude is always independent of magnetic field strength while strictly depends on its angle regarding the propagation direction.Both types of solitons (compressive o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…It will be recalled that this factor is related to the normalized linear phase speeds, which are given by c = 1/ √ 1 − β. As seen already in the discussion about (19), A can change sign at β c . For good measure, we include in Figure 1 a graph of how A and B vary as β is increased from 0 to 0.6.…”
Section: Basic Formalism and Generic Compositionsupporting
confidence: 54%
See 2 more Smart Citations
“…It will be recalled that this factor is related to the normalized linear phase speeds, which are given by c = 1/ √ 1 − β. As seen already in the discussion about (19), A can change sign at β c . For good measure, we include in Figure 1 a graph of how A and B vary as β is increased from 0 to 0.6.…”
Section: Basic Formalism and Generic Compositionsupporting
confidence: 54%
“…The coefficient of the quadratic nonlinearity, A, has already been encountered in a similar role in (19), except for factors (1 − β) which have been omitted there. It will be recalled that this factor is related to the normalized linear phase speeds, which are given by c = 1/ √ 1 − β.…”
Section: Basic Formalism and Generic Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this connection, Liu et al (1994) and Lima et al (2000) showed that plasma experimental results point to non-Maxwellian velocity distribution. Since that, the Tsallis q-entropy and the ensuing generalized statistics have been employed with some success in plasma physics (Du 2004;Liyan and Du 2008;Liu and Goree 2008;Tribeche 2010, 2011;Tribeche 2011a, 2011b;Bains et al 2011aBains et al , 2011bTribeche and Merriche 2011;Moghanjoughi 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The most well studied of such modes is the so-called "Dust Acoustic Wave" (DAW) which arises due to the restoring force provided by the plasma thermal pressure (electrons and ions) while the inertia is due to the dust mass. The Tsallis q-entropy and the ensuing generalized statistics have been employed with some success in plasma physics (Du 2004;Liyan and Du 2008;Liu and Goree 2008;Tribeche et al 2010;Amour and Tribeche 2010;Ait Gougam and Tribeche 2011;Bains et al 2011;Pakzad and Tribeche 2011;Abdelsalam et al 2011;El-Awady and Moslem 2011;Bacha and Tribeche 2011;Moghanjoughi 2011). Recently (Tribeche and Merriche 2011), we revisited the seminal paper of Mamun et al (1996) within the theoretical framework of the Tsallis statistical mechanics (Tsallis 1988).…”
mentioning
confidence: 99%